2018
DOI: 10.9767/bcrec.13.2.1585.320-330
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Production of Biodiesel from Rubber Seed Oil Using a Packed Bed Reactor with BaCl2 Impregnated CaO as Catalyst

Abstract: The goal of this research was to test barium chloride (BaCl2) impregnated calcined razor clam shell as a solid catalyst for transesterification of rubber seed oil (RSO) in a packed bed reactor (PBR). The waste razor clam shells were crushed, ground, and calcined at 900 °C in a furnace for 2 h to derive calcium oxide (CaO) particles. Subsequently, the calcined shells were impregnated with BaCl2 by wet impregnation method and recalcined at 300 °C for 2 h. The synthesized catalyst was characterized by X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…The CaO catalyst was chosen to support the reaction in the one-stage transesterification method. Buasri and Loryuenyong [27] obtained a maximum yield of 98.7% with the use of a 200 mm BaCl2/CaO catalyst bed. This selection is based on the fact that Ba2+ ions are highly alkaline when added to Ca2+ ions, resulting in high yields under low reaction conditions [42], [43].…”
Section: Quantitative Results Of One-stage Transesterification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CaO catalyst was chosen to support the reaction in the one-stage transesterification method. Buasri and Loryuenyong [27] obtained a maximum yield of 98.7% with the use of a 200 mm BaCl2/CaO catalyst bed. This selection is based on the fact that Ba2+ ions are highly alkaline when added to Ca2+ ions, resulting in high yields under low reaction conditions [42], [43].…”
Section: Quantitative Results Of One-stage Transesterification Methodsmentioning
confidence: 99%
“…Qualitatively, the molar ratio 4: 1 and 5: 1 has not provided biodiesel quality that met SNI 7182-2015 standards. In the one-stage transesterification method, Buasri and Loryuenyong [27] reported that the increase in biodiesel yield occurred at a ratio of 6: 1 to 12: 1. A further increase in the ratio will increase the yield, but a stable emulsion will be formed that is difficult to separate from biodiesel [50].…”
Section: Quantitative Results Of One-stage Transesterification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The agricultural, food, chemical, and energy industries could all stand to benefit eco nomically from the possibility of producing biofuel and heterogeneous catalysts through the utilization of waste oil and agricultural biomass [40].…”
Section: Modeling and Regression Of Biodiesel Process Using Annmentioning
confidence: 99%
“…The authors would also like to express their appreciation to the Department o Materials Science and Engineering, Faculty of Engineering and Industrial Technology at Silpakorn The agricultural, food, chemical, and energy industries could all stand to benefit economically from the possibility of producing biofuel and heterogeneous catalysts through the utilization of waste oil and agricultural biomass [40].…”
Section: Acknowledgmentsmentioning
confidence: 99%